(untitled) (Asian Journal of Plant Biology, 2021)
This study focuses on the anti-protozoan activities of Stachytarpheta angustifolia (Tarkajiya; Hausa, Devil’s coach whip; English) on haematological parameters of Albino Wistar rats which is an unexplored study area. The work is aimed at the determination of the effects of S. angustifolia on Wistar Rats, when exposed to herbal extract on the haematological parameters of Wistar Rats infected with E. tenella Biomarkers. The plant was obtained whole; dried under the shade, made into a powdered form and aqueous extraction method carried by maceration technique. After infecting the experimental animals with the parasites; E. tenella, the following respective doses of 750 mg and 1500 mg were administered to the rats in groups of 3 and 4. Results obtained were analyzed using Analysis of Variance (ANOVA). It was discovered that no significant harmful effect on the rats was recorded, but 60 % of the parasites were killed. This work demonstrated that the herbal extract killed the parasites but induced minimal stress to the animals as shown by the low haematological parameters in the study.